Back pain prevalence in adolescent athletes. (19th February 2016) - Müller, J.; Müller, S.; Stoll, J.; Fröhlich, K.; Otto, C.; Mayer, F.
Abstract : The research aimed to investigate back pain (BP) prevalence in a large cohort of young athletes with respect to age, gender, and sport discipline. BP (within the last 7 days) was assessed with a face scale (face 1–2 = no pain; face 3–5 = pain) in 2116 athletes (m/f 61%/39%; 13.3 ± 1.7 years; 163.0 ± 11.8 cm; 52.6 ± 13.9 kg; 4.9 ± 2.7 training years; 8.4 ± 5.7 training h/week). Four different sports categories were devised (a: combat sports, b: game sports; c: explosive strength sport; d: endurance sport). Analysis was described descriptively, regarding age, gender, and sport. In addition, 95% confidence intervals (CI) were calculated. About 168 (8%) athletes were allocated into the BP group. About 9% of females and 7% of males reported BP. Athletes, 11–13 years, showed a prevalence of 2–4%; while prevalence increased to 12–20% in 14‐ to 17‐year olds. Considering sport discipline, prevalence ranged from 3% (soccer) to 14% (canoeing). Prevalences in weight lifting, judo, wrestling, rowing, and shooting were ≥10%; in boxing, soccer, handball, cycling, and horse riding, ≤6%. 95% CI ranged between 0.08–0.11. BP exists in adolescent athletes, but is uncommon and shows no gender differences. A prevalence increase after age 14 is obvious. Differentiated prevention programs in daily training routines might address sport discipline‐specific BP prevalence.